Hydrodynamic forces and heat transfer of nanofluid forced convection flow around a rotating cylinder using finite element method: The impact of nanoparticles. (November 2019) - Hussain, Shafqat; Jamal, Muhammad; Ahmed, Sameh E.
Abstract: A computational approach is utilized to study the nanofluid forced convection flow around a rotating circular cylinder in a horizontal channel. Different types of nanoparticles in the base fluid are considered and investigated such as Silica ( S i O 2 ), Copper ( Cu ) and Alumina ( Al 2 O 3 ). Average Nusselt number ( Nu avg ) are compared for various conditions of the cylinder, namely adiabatic and isothermal cylinders respectively for two locations of cylinder. A dimensionless system of partial differential equations over a complex computational domain is discretized by applying the higher order stable finite element method. The discretized nonlinear system of algebraic equations is linearized using the Newton method. A geometric multigrid method is implemented for the computation of linearized subproblems in each nonlinear sweep. Impact of the pertinent parameters is investigated such as the Reynolds number (10 ≤ Re ≤ 200), angular velocity (−75 ≤ Ω ≤ 75) and the nanoparticles volume fraction (0.0 ≤ ϕ ≤ 0.04). Numerical results are demonstrated in the form of isotherms, streamlines and suitable graphs for various quantities of interest. It is inferred that the clockwise rotation of the cylinder makes the fluid move over the cylinder while the fluid moves below the cylinder in the anticlockwise case. Moreover, an increase in the nanoparticles volume fraction enhances the average Nusselt number and decreases both of the lift and drag coefficients.